Efektifitas Buku Referensi Media Pembelajaran Matematika Sekolah Menengah Pertama (SMP) - Sripatmi Sripatmi; Junaidi Junaidi; Nourma Pramestie Wulandari; Eka Kurniawan (Mandalika Mathematics and Educations Journal, 2023)
The purpose of this study is to determine the effectiveness of reference books for junior high school mathematics learning media. For this reason, a limited trial was carried out on 6 mathematics teachers at a junior high school in Mataram. This research uses a mixed approach or Mix methods. The research instrument consists of test instruments and interview guidelines about junior high school mathematics teachers' knowledge of junior high school learning media. The results of this study are Based on the data that has been melted and the wetting that has been carried out , significant differences in knowledge before and after studying junior high school mathematics learning media books , it can be concluded that junior high school mathematics learning media books are effective in increasing teacher knowledge in learning media, especially on knowledge about the benefits and functions of learning media, types of learning media, concept maps, interactive power points, student worksheets, props, and tools for creating junior high school math learning videos.